THE EFFECT OF WORKPLACE WELL-BEING AND MENTAL HEALTH ON EMPLOYEE PERFORMANCE - Solihin; Eli Ahmad Mahrini; Sekar Fauzia Larasati; Mochamad Anjar Albagja (Politeknik Mardira Indonesia, 2025)
companies operate actively in designing and solving strategic problems as well as have responsibility to business goals. In order to good employee performance, companies need to pay attention to employee well-being and mental health. This study aims to find out the impact of workplace well-being and mental health on employee performance at UD Putra TS Majalengka.The method used in this research is quantitative research. The population in this study is an employee of UD Putra TS Majalengka, sampling using simple random samplings with a total of 80 employees. The research uses data collection techniques in the form of questionnaires derived from the likert scale. The data analysis technique used in this study is using IBM SPSS 26 software. The results of this study show that workplace well-being has a high category, mental health has a good category, and employee performance has a high category. Partally, workplace well-being has a positive and significant effect on employee performance, mental health has a positive and significant effect on employee performance Keywords : workplace well-being and mental health have, employee performance.